Literatur Review : Peluang dan Tantangan Metaverse - Achmad Solechan; Toni Wijanarko Adi Putra (LPPM Politeknik Pratama Kendal, 2022)
This research was conducted because of the importance of the metaverse in its contribution to increasing GDP. Metaverse business growth in the last 10 years compared to GDP has contributed 2.8% globally. This is what is interesting to study regarding the opportunities and challenges faced in the application of the metaverse. This research was conducted by using a literature review review to obtain a theoretical basis that could support solving a problem that is being or will be studied. Opportunities and challenges of the metaverse in the literature review can be concluded that previous researchers have used a good research methodology using a good theoretical basis and research steps. Most studies show that the metaverse is still in demand as a topic of interest by well-known research and is still a trending theme in the research world. The application of the metaverse platform covers multi-disciplinary fields, including education, health, business/marketing, games, information systems, concerts, fashion events, advertising, virtual real estate ownership etc. This research suggestion needs a detailed discussion of the problems and challenges faced in the Metaverse application in the coming period, in the next 10 years it is predicted that the metaverse will still be a hot topic of conversation globally, the need for metaverse development in various fields, and the need for copyright, brand rights and trade rights in relation to the metaverse-based application platform.